Pengaruh Periklanan, Publisitas Dan Promosi Penjualan Terhadap Keputusan Pembelian Konsumen (Studi Kasus Pada Konsumen UMKM Ikan Asap Demak) - Shofif Sobaruddin Akbar; Mochamad Fadjar Darmaputra (UNIVED Press, 2022)
This research is motivated by the existence of a business phenomenon that is being experienced by UMKM Demak smoke fish. The purpose of this study to analyze the influence of advertising, publicity and sales promotion of consumer purchasing decisions. The sample of research is 150 respondents. By using Purposive Sampling method with the criteria of consumers who have made a purchase of smoked fish in UMKM Demak, respondents who have a minimum age of 18 years, respondents who are easy to find and want to fill out the questionnaire and is a direct buyer. This research uses multiple regression analysis tool. The result showed that advertising, publicity, and sales promotion had an effect on purchasing decision.